Ethanol extracts of Cassia grandis and Tabernaemontana cymosa inhibit the in vitro replication of dengue virus serotype 2 (2015)
To determine the antiviral activity of ethanol extracts derived from Cassia grandis leaves and Tabernaemontana cymosa bark against two dengue virus (DENV) serotype 2 strains DENV-2/NG and DENV-2/16681 in two cell lines susceptible to infection...